First Report of a Neotropical Agaric (Lepiota spiculata, Agaricales, Basidiomycota) Containing Lethal α-Amanitin at Toxicologically Relevant Levels - Angelini, Claudio; Vizzini, Alfredo; Justo, Alfredo; Bizzi, Alberto; Davoli, Paolo; Kaya, Ertuğrul (Frontiers in Microbiology, 2020)
A recent collection of Lepiota spiculata from the Dominican Republic is presented here. Macro- and micromorphological features of L. spiculata are described in detail and its evolutionary (phylogenetic) position within Lepiota sect. Ovisporae, in the subincarnata / brunneoincarnata clade is assessed on the basis of a combined nrLSU+nrITS+rpb2+tef1 analysis. Additionally, high levels of deadly amatoxins were detected and quantified in L. spiculata for the first time by HPLC analysis; in particular, α-amanitin was found at concentrations up to approx. 4 mg/g dry weight, which render L. spiculata a potentially lethal mushroom, if ingested.